Exploring the Application of Differentiated Learning in Elementary Schools - Triyanti, Adelia; Heryati, Lutfi; Dewi, Gita Sandra; Mascita, Dede Endang; Rahayu, Ira (PT Inovasi Pratama Internasional, 2024)
This study aims to explore differentiated learning in each school and describe the implementation of differentiated learning in the classroom. The method used is qualitative descriptive. Differentiated learning data is learning that accommodates student learning needs. Teachers provide facilities to students according to their needs, because each student has different characteristics, so they cannot be given the same treatment. collected based on the results of interviews with 4 elementary school teachers in Cirebon City, Indonesia. The results of conceptual research reveal that there is a differentiated learning goal is to coordinate learning by paying attention to learning interests, learning readiness and learning preferences, helping all students in learning so that learning goals can be achieved by all students increasing student motivation and learning outcomes establishing harmonious relationships between teachers and students so that students can be more enthusiastic in learning, helping students become independent learners so that Being an individual who is accustomed and also has an attitude of respect for diversity, increases teacher satisfaction because there is a sense of challenge to want to develop their teaching skills so that teachers will become more creative. It can be concluded that differentiated learning provides opportunities for students to be able to learn naturally and efficiently with teachers who are able to collaborate on the methods and approaches needed. This research is important to discuss because we can find out the process of differentiated learning in each elementary school we studied